O USO DE MATERIAIS MANIPULÁVEIS COMO FERRAMENTA NA RESOLUÇÃO DE PROBLEMAS TRIGONOMÉTRICOS - Santos, Darcson Capa dos (2011)
This research investigated the use of manipulatives as a tool for exploring mathematical concepts, in solving problems of trigonometry. The work was developed with a tutoring class, of 2nd year of high school, in a state school in the city of Uruguaiana, RS. It was intended to examine whether students with difficulties in mathematics may, through use of models, have aroused the skills of questioning, hypothesizing and developing autonomous resolutions of problems in trigonometry. The research approach is qualitative, based on observations of the activities developed by students and applications of questionnaires. In each activity performed, problems were set out and were solved with the aid of the models constructed by the teacher-researcher or by the students themselves. The methodology of problem solving was adapted from proposals of Brazilian and foreign authors. Students' responses and their analysis were presented in detail. It was noted that most students had a significant advantage of tutoring and, in particular, appreciated the performance of activities, materials construction and the possibility of interaction with colleagues. It is considered that this experience can be utilized in the classroom, and thus we produced a set of activities that is presented as the product of this dissertation.